Landscape Values in a Marina in Granada (Spain): Enhancing Landscape Management through Public Participation - Ricardo Martín; Víctor Yepes (Land, 2023)
Landscape values are related to the attributes that people assign to a perceived landscape. They reflect marina user perceptions, thus representing a feedback tool for marina managers to use to verify the degree of user satisfaction. This study focused on identifying and assessing a marina’s landscape values. We took Marina del Este (Granada, Spain) as a case study. We considered interviews and a questionnaire to devise methods to enhance the participation of stakeholders and users. First, the SWOT analysis from stakeholder interviews enabled us to collect management’s perceptions. Second, the survey gathered the marina’s landscape values, comprising 104 respondents from visitors and users. ANOVA and PCA methods were applied to check the suitability of the values. The results showed that the marina should be in keeping with an atmosphere of tranquility and well-being. Nevertheless, there was a need to improve values related to nautical tourism, such as hospitality and maintenance, dealing with the lack of space and an excess of urbanization in the surroundings. Marina managers should consider these outcomes and analyze the points of improvement to establish the causes of these disagreements and propose solutions for the established management model. The perception of stakeholders and users can enable more consensual policies with greater levels of acceptance and involvement.